Peran Gereja dan Hamba Tuhan Dalam Menghadapi Tantangan Era Digital - Ferry Simanjuntak; Roni Kurniawan; Eston Santoso; Mindra Senjaya; Devi Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2026)
The church is in such a massive digital technology change that it must be ready to face various new challenges that arise from the transformation process. The role of God's servants is increasingly important and strategic in the church's ministry to face these challenges. For this reason, community service activities in the form of seminars are carried out to equip God's servants in the city of Bekasi. In this activity, God's servants were equipped with various materials, including Understanding the Challenges of the Church in the Digital Era, Spirituality of God's Servants in the Current Era, Dynamic Capabilities of God's Servants in Facing the Challenges of the Digital Era, and Family Discipleship are the main pillars of the Church in facing the challenges of this era. The participants of this activity gave a positive response and enthusiasm in participating in the entire session of this activity so that it is hoped that this activity can open and increase the insight of God's servants in the local church ministry.